HUBUNGAN KELELAHAN KERJA DENGAN PRODUKTIVITAS KERJA PADA PEMETIK TEH DI PT PERKEBUNAN NUSANTARA IV BAH BUTONG KABUPATEN SIMALUNGUN TAHUN 2014 - ivory inderani; lina tarigan; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Fatique is one of the risks that causes the decrease in workers’ health level. Work fatique will decrease workers’ performance which will eventually decrease work productivity. Work fatique is indicated by the weakening of workers in doing their work or activities so that they make errors in doing their work, and job accident will fatally occur. The research was an analytical survey with cross-sectional design which was aimed to find out the correlation between fatigue in working and work productivity in tea pickers at PT Perkebunan Nusantara IV Unit Kebun Bah Butong, Subdistrict of Sidamanik, District of Simalungun in 2014. The population is all the 80 tea pickers using scissors in the four afdelings, afdeling III and afdeling IV, and 35 of them were used as the samples, taken by using purposive sampling technique.  Work fatique is measured with the Flicker Fusion. Work productivity is calculated from the tea leves produced:  60 kilograms/ day/ person. Exact Fisher statistic test was used to find out the correlation between the independent variables and dependent variable. Based on the fatigue of the respondents, it was found that, 20 respondents (57,1%) were tired, and 15 respondents (42,9%) were not, based on the measurement by Flicker Fusion device. Based on the distribution frequency of work productivity, it was found that 25 respondents (71.4%) matched and 10 respondents (28.6%) did not. From the result of Exact Fisher test, it was found that p-value = 0.022 (p < 0.05) which indicated there was significant correlation between fatique and work productivity. If a worker’s productivity was disturbed due to the physical and psychological fatique, there would be the decrease in productivity. Work fatique can increase the risks for errors, accidents and injuries. It is suggested that the workers manage their fatique so that their work productivity will increase. Workers’ work productivity is related to the payment and length of work time per day. The company should pay attention to good payment system to increase work productivity.